Nurse-led care interventions for high blood pressure control: Implications for non-communicable disease programs in Uganda - Godfrey Katende; Kathleen Becker (Elsevier, 2016)
Objective: The aim of the integrative review was to assemble the best available evidence for effective nurse-led care interventions for high blood pressure control (HBP) and, then seeks to identify effective evidence based strategies for adaptability in non-communicable disease programs in Uganda. Material and methods: A literature review of 18 articles was undertaken using the Medical subject terms "hypertension/nurse", "Sub-Saharan Africa", "Nurse-led/Nurse run clinics" in Medline via PubMed and the Cochrane Central register of Controlled trials. We then set the search limits to include articles published in English, past five years, involving only human subjects and adults. Only articles that employed an intervention and involved a nurse/pharmacist or physician in primary, secondary and acute care setting were included for the study. The level and strength of the articles was appraised by using the Johns Hopkins Nursing Evidence-based practice appraisal tools. Results: There is strong evidence to support nurse-led care interventions to be effective in the control of high blood pressure (HBP). There are a number of effective evidence based strategies for HBP control used by the nurses; patient/provider education, patient/provider reminder system, nurse prescribing, team based care, home BP monitoring and use of treatment algorithms. Conclusion: Nurses play a significant role in the control of high blood pressure when they employ effective evidence based strategies in identification, prevention and management of hypertension. Adapting effective evidence based strategies in identification, prevention and management of non-communicable diseases could improve patient outcomes in Uganda.